Avaliação do impacto do uso da fruta da Mangifera indica L. (manga) no tratamento de crianças anêmicas fazendo uso de sulfato ferroso - Oliveira, Susy Mary Souto de (2010)
Iron deficiency is long a serious health problem, even in its moderate form, especially for its consequences reflected in the productive capacity of individuals and in the cognitive development of children. This occurs in approximately 50% of Brazilian children and represents the second nutritional problem in the United States, jeopardizing the economic and social development of the nation. Diet rich in iron, vitamin C, vitamin A and iron supplementation with ferrous sulfate as universal treatment are among the preventive measures. Currently, the use of foods with health properties has grown among the population as a means to minimize side effects and high costs of drug treatment. In this context, the purpose of this study was to investigate the impact of using Mangifera indica L. (mango) in the treatment of anemic children making use of ferrous sulfate. The study was conducted with 50 children from both genders, with mild anemia at the age range from one (1) to six (6) years attending to three kindergarten Reference Centers in the city of Joao Pessoa selected for convenience, after signing the Free and Clear Consent Term (Process No. 1273 / CEP / CCS) by their parents or guardians. The children were divided into two groups: intervention group, treated with mango pulp (60% pulp) and Control group, treated with artificial juice containing 1% of mango pulp. The treatment for both groups was daily, four days a week during meals for 60 days. During the same period, all the children made use of ferrous sulfate. All children were clinically evaluated and submitted to biochemical analysis at baseline and after 60 days of treatment. The analysis of data included the Epi Info statistical program version 6.04 for assessment of the nutritional status and the R Development Core Team for further analysis. The hemoglobin, hematocrit, serum iron, ferritin, PCR and serum retinol values, as well as the nutritional status were compared before and after treatment in both groups, verifying that hematocrit, ferritin, serum retinol, PCR and serum iron values for the control group remained in clinical normality, except for serum iron values, which were reduced in the intervention group before treatment, normalizing after intervention. Significant reduction in mean PCR values was observed for both intervention and placebo groups and increased hemoglobin and hematocrit. Regarding the nutritional status, significant weight gain in children from the intervention group was observed. In conclusion, the use of Mangifera indica L juice (mango) presents no health properties against anemia in children with normal serum retinol values making use of ferrous sulfate.